THE ROLE OF ECOLOGICAL INNOVATIONS IN THE TRANSFORMATION OF TOURISM ENTERPRISES (INNOVATIVE ECONOMY, 2025)
Brych V.Ya., Petrukha N.M. THE ROLE OF ECOLOGICAL INNOVATIONS IN THE TRANSFORMATION OF TOURISM ENTERPRISESPurpose. The aim of the article is to single out and systematize existing ecological innovations in the tourism industry.Methodology of research. The study was conducted using the methods of scientific knowledge. The study used the method of statistical data analysis to assess the level of pollution from tourism activities, the method of comparative analysis ‒ to identify the benefits and risks of introducing environmental innovations, and the method of systematisation ‒ to identify the most popular environmental innovations among tourism enterprises.Findings. As part of the study, the author analysed the level of pollution from tourism activities, which confirmed a significant disparity in CO2 emissions between countries with high population mobility and less developed regions. The main benefits of environmental innovations for tourism enterprises, such as cost reduction, increased competitiveness and improved reputation, as well as key risks, such as high initial investment and regulatory restrictions, are identified. The article systematises environmental innovations, among which the most popular are carbon-neutral accommodation, regenerative tourism, blockchain for transparency, artificial intelligence for sustainable tourism, clean transport, virtual and AR technologies, biophilic design, alternative packaging, etc. It is found that the level of implementation of environmental innovations in tourism activities remains insufficient due to economic and organisational barriers.Originality. For the first time, the benefits and risks of introducing environmental innovations in tourism activities for three institutional levels are systematised: tourism enterprises, territorial communities and the state.Practical value. The results of the study can be useful for tourism enterprises, government agencies, local communities and scientists in developing sustainable development strategies and implementing environmental innovations.Key words: ecotechnology, sustainable tourism, pollution, virtual and AR technologies, clean transport, artificial intelligence, tourists.
Keywords: ecotechnology; sustainable tourism; pollution; virtual and AR technologies; clean transport; artificial intelligence; tourists